GENERAL EQUILIBRIUM AND ECONOMIC EFFICIENCY IN ECONOMY - Salayeva Quvonchoy Rustam qizi (Web of Journals Publishing, 2024)
This article is about terms, general equilibrium and economic efficiency which are fundamental concepts in economics that play a crucial role in shaping the functioning of an economy. These concepts are closely intertwined and are essential for ensuring optimal resource allocation and overall welfare in a market system.
Keywords: equilibrium, efficiency, resource allocation, welfare, Pareto efficiency.